Pedagogical model for implementing drone racing into the sports life of a university - Dubrov A.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop and scientifically substantiate a pedagogical model for the use of innovative pedagogical technologies for the introduction of drone racing into the inclusive physical education and sports environment of the university. Methods and structure of the study. The comparative analysis and synthesis of special documentation and information sources; modeling organizational and methodological support for the introduction of drone racing into the physical education and sports space of the university; structuring and integration of pedagogical technologies; formulation of conclusions. Results and conclusions. The pedagogical model for the use of innovative pedagogical technologies for the effective implementation of drone racing in inclusive student sports has been developed and scientifically substantiated in order to involve student youth in the system of sports training and participation in competitions.